Analisis Faktor Yang Mempengaruhi Kelengkapan Resume Medis Rawat Jalan Di Rs Sumber Waras Kabupaten Cirebon - Weryco Latupeirissa, Loura; Setiawan, Dede (Awatara Publisher, 2024)
Completeness of medical records is important because it influences the service process provided by health workers and has an impact on the quality of service in a hospital. A medical record containing a medical resume is said to be complete if it is filled 100%. This research is an observational study and uses a cross sectional design. The sample to determine the completeness of the outpatient medical record resume was 53 documents and to determine the factors that influence the completeness of the outpatient medical resume, namely all doctors at Sumber Waras Hospital were 53 people. The results of this research were that outpatient medical resumes were 24 documents complete and 29 documents were incomplete. For the completeness knowledge variable, a p value of 0.025 was obtained. (0.025 < 0.05), then knowledge influences the completeness of the medical resume, on the attitude variable with a completeness p value of 0.027. (0.027 < 0.05), then attitude influences the completeness of the medical resume, and for the behavior and completeness variables, a p value of 0.025 is obtained. (0.025 < 0.05) then behavior influences the completeness of a medical resume.